Acidity effect in pollen germination and tube length of Prunus Amygdalus Batsch and Prunus domestica L. - Gür, Nazmi; Ay, Esma; Topdemir, Aykut (My University, 2016)
Pollen tube germiantion and elongation an indicator of environmental pollution. In this study, in vitro pollen germination of Prunus amygdalus Batsch ve Prunus domestica L. species was examined at ten different levels of pH using Brewbaker and Kwack's medium. Pollen germination and pollen tube length was measured after 4/5 hrs at 22±1 oC of culturing. Results showed, the pollen germination rate was higher in decreased pH level in both species studied at 2.8 pH. The maximum germination was observed at 6.4 pH.
Bildiri - Yayımlanmış
Keywords: Prunus amygdalus Batsch; Prunus domestica L; Pollen germination; Pollen tube elongation